Environmental DNA captures elasmobranch diversity in a temperate marine ecosystem. Issue 5 (24th March 2022) - Liu, Zifang; Collins, Rupert A.; Baillie, Charles; Rainbird, Sophie; Brittain, Rachel; Griffiths, Andrew M.; Sims, David W.; Mariani, Stefano; Genner, Martin J.
Abstract: Many sharks, skates, and rays (elasmobranchs) are highly threatened by the activities of commercial fisheries, and a clear understanding of their distributions, diversity, and abundance can guide protective measures. However, surveying and monitoring elasmobranch species can be highly invasive or resource‐intensive, and utilization of non‐invasive environmental DNA‐based methods may overcome these problems. Here, we studied spatial and seasonal variation in the elasmobranch community of the Western English Channel using environmental DNA (eDNA) collected from surface and bottom waters periodically over an annual cycle (2017–2018). In total we recovered 13 elasmobranch species within eDNA samples, and the number of transformed eDNA reads was positively associated with species (hourly) catch data resolved from 105‐year time series trawl data (1914–2018). These results demonstrate the ability of eDNA to detect and semi‐quantitatively reflect the prevalence of historically dominant and rare elasmobranch species in this region. Notably, eDNA recorded a greater number of species per sampling event than a conventional trawl survey in the same area over the same sampling years (2017–2018). Several threatened species were recovered within the eDNA, including undulate ray, porbeagle shark, and thresher shark. Using eDNA, we found differences in elasmobranch communities among sampling stations and between seasons, but not between sampling depths. Collectively, our results suggest that non‐invasive eDNA‐based methods can be used to study the spatial and seasonal changes in the diversity and abundance of whole elasmobranch communities within temperate shelf habitats. Given the threatened status of many elasmobranchs in human‐impacted marine environments, eDNA analysis is poised to provide key information on their diversity and distributions to inform conservation‐focused monitoring and management. Abstract : Sharks, skates, and rays are highly threatened by commercial fisheries, and reliable information on species distributions and diversity can guide protective measures. Here, we evaluated the ability of environmental DNA (eDNA) to quantify the diversity of sharks, skates, and rays of the English Channel. We found eDNA was able to reflect the relative abundance of species and detect threatened species, suggesting a future role of eDNA in monitoring and management of this species group.